2011
DOI: 10.1002/j.2334-5837.2011.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

7.1.1 Modeling Pilot Workload for Multi‐Aircraft Control of an Unmanned Aircraft System

Abstract: Abstract.A demand for increased use of Unmanned Aircraft Systems (UASs) without commensurate increases in pilot manpower has created proposals for the concept of Multiple Aircraft Control (MAC). To understand the potential effect of such proposals, a workload model was developed from pedigreed system architecture which permits the prediction of the effects of MAC on individual pilot workload levels. Results indicate multiple critical factors that affect the implementation of MAC. Although the model suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When considering MAC, past research has identified several challenges to include dynamic and emergency task saturation, communications interruptions, and effective and efficient transfer of operational SA from a losing pilot to a gaining pilot [3]. This SA transfer occurs at the conclusion of a typical shift and is termed "change-over".…”
Section: A Cognitive Task Analysis-based Evaluation Of Remotely Pilotmentioning
confidence: 99%
See 3 more Smart Citations
“…When considering MAC, past research has identified several challenges to include dynamic and emergency task saturation, communications interruptions, and effective and efficient transfer of operational SA from a losing pilot to a gaining pilot [3]. This SA transfer occurs at the conclusion of a typical shift and is termed "change-over".…”
Section: A Cognitive Task Analysis-based Evaluation Of Remotely Pilotmentioning
confidence: 99%
“…This SA transfer occurs at the conclusion of a typical shift and is termed "change-over". Analyses have concluded that change-over activities can consume up to 10% of a pilot's mission time [3]. In a MAC scenario, if a pilot accepts control of three or four aircraft, the subsequent transfer time and effort can balloon to consume an unreasonable percentage of the pilot's effective mission time.…”
Section: A Cognitive Task Analysis-based Evaluation Of Remotely Pilotmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of a single operator overseeing multiple agents in multi-HAT missions, cognitive overload may occur. During simulated ISR missions in which an operator controlled four vehicles which were navigating and communicating in a benign setting, workload was found to exceed the acceptable limit for a majority of the mission, resulting in mission degradation, particularly any time communication was needed ( Schneider et al, 2011 ). Furthermore, workload can increase as the reliability of an autonomous teammate decreases as operators take more manual control ( Chen and Barnes, 2012 ).…”
Section: Introductionmentioning
confidence: 99%